Dynamics of Content Development in the Digital Broadcast Environment - Udoudom Uduak Imoh; Nwokeocha Ifeanyi M (IJRAEL: International Journal of Religion Education and Law, 2023)
The dynamics of content development in the digital broadcast environment have been shaped by the rapid advancement of technology and the increasing availability of digital platforms for content creation and distribution. This has led to significant changes in the ways in which content is created, distributed, and consumed, and has challenged traditional models of content development and distribution. The purpose of this research is to explore the development of content in digital broadcast environments. The focus of the study is on the impact of digital technology on the creation, distribution, and consumption of broadcast content. This research aims to identify the challenges and opportunities that content creators face in the digital age and to provide insights into the evolving role of content development in the digital broadcast landscape. The study employs a desk research methodology, that include a comprehensive review of relevant literature. The study indicate that digital technology has greatly expanded the reach and accessibility of broadcast content, enabling content creators to reach a global audience. However, the increased competition in the digital space has also presented new challenges, such as the need for more innovative and engaging content, as well as the need to effectively monetize digital content. Overall, this research highlights the importance of adapting to the changing digital environment for content creators and the broadcast industry. It provides insights into the future of content development in the digital era, suggesting that success in the digital broadcast environment will depend on the ability to embrace new technology, effectively monetize content, and continuously create engaging and innovative content.